Effects of microgravity on neuromuscular control of the spine: a protocol for a systematic review and meta-analysis - Deborah Falla; Valter Devecchi; Michail Arvanitidis (BMJ Open)
Introduction As spaceflight missions become more frequent and prolonged, the effects of microgravity on the musculoskeletal system represent a critical concern for astronauts’ health given their increased risk of spinal pain and injury. A better understanding of the adaptations induced by microgravity on neuromuscular control of the spine is essential to guide the development of effective countermeasures. Thus, this systematic review will aim to investigate the effects of microgravity on the neuromuscular control of the spine.Methods and analysis This protocol has been developed following the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols. MEDLINE, EMBASE, CINAHL, Web of Science, PubMed, grey literature and specialised space research resources will be searched from inception up to December 31, 2024. Screening processes, data extraction and risk of bias assessment will be conducted by two independent reviewers. Studies investigating the acute and long-term effects of microgravity on neuromuscular control of the spine will be included. Studies investigating spaceflight conditions or other protocols simulating microgravity, such as parabolic flights, dry immersion and long-term bed rest, will be considered eligible. Non-randomised studies of intervention with before-and-after design will represent the main studies of interest, and their risk of bias will be evaluated with the Risk Of Bias In Non-randomised Studies-of Interventions tool. Random-effect meta-analyses will be conducted for quantitative synthesis when clinical and methodological consistency is ensured. The certainty of evidence will be evaluated using the Grading of Recommendations, Assessment, Development and Evaluation guidelines.Ethics and dissemination As this systematic review is based on previously published studies, no ethical approval is required. The findings will be disseminated through publication in an international peer-reviewed journal and presented at conferences. All data relevant to the study will be included in the article or uploaded as supplementary information.PROSPERO registration number CRD42024608544.